Proses Bioakumulasi dan Biotransfer Merkuri (Hg) pada Organisme Perairan di dalam Wadah Terkontrol - Markus Talintukan Lasut (Jurnal Matematika & Sains, 2009)
A study to show bioaccumulation and biotransfer processes of mercury (Hg) has been done in controlled experimental chambers. Three groups of aquatic organisms, namely phytoplankton Nannochloropsis oculata representing producers, fish Lebistes (Poecilia) reticulatus representing herbivorous consumers, and fish Tiger Fish Symphysodon sp. representing carnivorous consumers, were contaminated by two different concentrations of Hg, in form of methylmercury (MeHg), such as 22.6 ppb as Treatment 1 and 79.1 ppb as Treatment 2. Controls were setup for all experiments. The result showed that bioaccumulation process occurred in the experiments and the amount of MeHg accumulated was depended on the amount of supplied MeHg. Biotransfer of MeHg was also indicated in this study. The highest biotransfer of MeHg occurred between the phytoplankton and the herbivorous fish pathway. The study concludes that bioaccumulation and biotransfer processes of MeHg occurred in the experimental pathway and the amount of mercury accumulated and transferred was depended on the amount of mercury supplied.